The shift in Russian trade during a year of war - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
This note examines changes in Russia's foreign trade during the past year. We discuss general trends in Russia's trade based on estimates constructed from mirror statistics and developments in EU-Russia trade. The detailed analysis of Russia's technology imports includes a selection of goods subject to EU export restrictions. We find substantial fluctuations in Russia's trade flows and changes in its geographical structure. EU trade with Russia has generally declined substantially and Russia is not an important export market for most EU countries. Our findings suggest that Russia has been unable to find viable substitutes for many EU imports at the aggregate level and most individual technology goods subject to EU export restrictions. Other countries have stepped into the breach and increased their exports to Russia, and in the case of certain products, their exports even exceed the comparable imports lost from the EU.
urn:nbn:fi-fe2023042638857
Keywords: 330; Russia; Ukraine; trade; sanctions